2021
DOI: 10.7454/jki.v24i1.690
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Study on the Experience of Male Nurses in Caring for Female Patients

Abstract: Nurses provide care equally and do not discriminate between men and women. However, male nurses face challenges and obstacles, especially when they take care of female patients. This study aimed to explore the experiences of male nurses who look after female patients by using a descriptive qualitative design with a phenomenological approach. Ten male nurse participants aged 26-43 years and having an experience of caring for female patients for at least 2 years were included in this study. Seven themes were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 8 publications
1
13
0
1
Order By: Relevance
“…23 In Indonesia, despite experiencing several obstacles, this set of nurses had higher self-efficacy levels and were usually just as caring as their female counterparts or even better. 21,35 An imbalanced number was observed between the male and female respondents, with the females being higher. Due to the high level of studies in an East Java district and the culture of respect for patients and families, men were seen to be just as caring as women.…”
Section: Resultsmentioning
confidence: 99%
“…23 In Indonesia, despite experiencing several obstacles, this set of nurses had higher self-efficacy levels and were usually just as caring as their female counterparts or even better. 21,35 An imbalanced number was observed between the male and female respondents, with the females being higher. Due to the high level of studies in an East Java district and the culture of respect for patients and families, men were seen to be just as caring as women.…”
Section: Resultsmentioning
confidence: 99%
“…Patients described them as exceptional caregivers who offered high-quality nursing care, and they expressed appreciation for their compassionate abilities [1,3,19,23,25]. Patients also reported a growing trust in male nurses, perceiving their presence as increasingly common [13,25]. Male nurses were seen as respectful of patients' need for comprehensive information about treatment modalities and a desire to engage with family members [5].…”
Section: Sex Preference and Care Providedmentioning
confidence: 99%
“…Some analyzed studies indicated that patients were more content with care received from male nurses than female nurses, citing qualities such as kindness and compassion [3,24,27]. However, two studies found no signi cant difference in satisfaction ratings between male and female patients when cared for by male or female nurses [13,19]. Notably, variables like politeness, courtesy, and patient comfort were statistically signi cant for male and female nurses [2].…”
Section: Sex Preference and Care Providedmentioning
confidence: 99%
See 2 more Smart Citations